Reclassification of Pterulaceae Corner (Basidiomycota: Agaricales) introducing the ant-associated genus Myrmecopterula gen. nov., Phaeopterula Henn. and the corticioid Radulomycetaceae fam. nov. - Caio A. Leal-Dutra; Gareth W. Griffith; Maria Alice Neves; David J. McLaughlin; Esther G. McLaughlin; Lina A. Clasen; Bryn T. M. Dentinger (IMA Fungus)
Abstract Pterulaceae was formally proposed to group six coralloid and dimitic genera: Actiniceps (=Dimorphocystis), Allantula, Deflexula, Parapterulicium, Pterula, and Pterulicium. Recent molecular studies have shown that some of the characters currently used in Pterulaceae do not distinguish the genera. Actiniceps and Parapterulicium have been removed, and a few other resupinate genera were added to the family. However, none of these studies intended to investigate the relationship between Pterulaceae genera. In this study, we generated 278 sequences from both newly collected and fungarium samples. Phylogenetic analyses supported with morphological data allowed a reclassification of Pterulaceae where we propose the introduction of Myrmecopterula gen. nov. and Radulomycetaceae fam. nov., the reintroduction of Phaeopterula, the synonymisation of Deflexula in Pterulicium, and 53 new combinations. Pterula is rendered polyphyletic requiring a reclassification; thus, it is split into Pterula, Myrmecopterula gen. nov., Pterulicium and Phaeopterula. Deflexula is recovered as paraphyletic alongside several Pterula species and Pterulicium, and is sunk into the latter genus. Phaeopterula is reintroduced to accommodate species with darker basidiomes. The neotropical Myrmecopterula gen. nov. forms a distinct clade adjacent to Pterula, and most members of this clade are associated with active or inactive attine ant nests. The resupinate genera Coronicium and Merulicium are recovered in a strongly supported clade close to Pterulicium. The other resupinate genera previously included in Pterulaceae, and which form basidiomes lacking cystidia and with monomitic hyphal structure (Radulomyces, Radulotubus and Aphanobasidium), are reclassified into Radulomycetaceae fam. nov. Allantula is still an enigmatic piece in this puzzle known only from the type specimen that requires molecular investigation. A key for the genera of Pterulaceae and Radulomycetaceae fam. nov. is also provided here.